Gait parameter changes during 10000 metre treadmill running - Hanley, B.; Mohan, A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to measure the effects of fatigue on gait parameters during running. Research has shown that changes due to fatigue include those of step length, cadence, flight time, and joint angles. Thirteen male distance runners ran 10000 m at a pace equivalent to 103% of their personal best time. Kinetic data was collected using a Gaitway treadmill (1000 Hz), and kinematic data using two RedLake MotionPro highspeed cameras (250 Hz). Data was collected at five points. Repeated measures ANOVA showed that there were significant differences in maximum force, impulse, and contact time (p < .01). Dependent t-tests showed a significant difference for the knee angle at take-off (p < .01). The kinetic and temporal changes occurred as early as 3000 m. Athletes are recommended to race at a constant pace to reduce the effects of fatigue.